Healing Fair Dealing? A Comparative Copyright Analysis of Canada's Fair Dealing to U.K. Fair Dealing and U.S. Fair Use - D’Agostino, Giuseppina (McGill Law Journal, 2008)
Giuseppina D’Agostino, 2008 53-2 McGill Law Journal 309, 2008 CanLIIDocs 166